ANTHRAQUINONES-A Naturopathic Compound - Nida, Tabassum Khan (Journal of New Developments in Chemistry, 2019)
Anthraquinones is a potent aromatic compound that besides being used commercially it offers numerous therapeutic benefits such as inhibits cancer growth by inducing apoptosis, relive constipation, ease bowl movement etc. Anthraquinones are found naturally in some plants such as senna, buckthorn, yellow dock etc while it can also be produced using chemical routes such as anthracene oxidation, naphthalene oxidation, condensation of 1, 4-naphthoquinone with butadiene etc. However its intake should strictly be regulated since it may cause some serious side effects.
Keywords: Bianthrones; Buckthorn; Cascara sagrada; Anthracene; Peristalsis; Laxative.